Information Search and Purchase Intention for "Made in China "Products by Ethnicity - Huang, Huat Wei; Ernest Cyril, de Run; Hiram, Ting (2016)
The objective of this research is to examine perception towards the products “Made in China” between the Malays and Chinese. Specifically, it looks into relationship between country-of-origin (COO) image, product knowledge, product involvement with information search and purchase intention. It further examines the difference of perception between the Malays and Chinese with their respective ethnic identification. A total of 550 questionnaires were distributed at a Public Institution of Higher Learning. 252 copies from the Malay respondents and 251 copies from Chinese were subsequently collected. Statistical tests of relationship and difference in SPSS 21.0 were used. The findings show that there is significant difference between COO image and product involvement among the Malay and Chinese respondents. Besides, there is difference between COO image and product knowledge among the Malays with strong and weak ethnic identification. As for the Chinese, the difference between strong and weak ethnic identification is found in COO image. In addition to the magnitude of ethnicity, this study also underscores the importance to understand customers’ product involvement due to its effect on information search and purchase intention.